Engineered small intestinal system as an alternative to in-situ intestinal permeability model. (April 2018) - Parthasarathi, S.; Bhushani, J. Anu; Anandharamakrishnan, C.
Abstract: Intestinal permeability is the most important factor that determines the bioavailability. In-vitro techniques like Caco-2 model and Ussing chamber are used for evaluating the intestinal permeability of the bioactive compound. But the lack of mucosal layer in those models makes the intestinal absorption prediction less accurate. We developed an engineered small intestinal system to evaluate intestinal permeability of bioactive compound. Following this approach, we have evaluated the intestinal permeability of fat soluble and water soluble bioactive compound and compared with in situ single-pass intestinal perfusion technique. Highlights: This study reports an 'engineered small intestinal system'. The system is proposed as an alternative to the in-situ intestinal permeability model. Permeability of two model compounds (lipophilic and hydrophilic) is demonstrated. The results are compared with the existing in-situ intestinal perfusion assay.